2010
DOI: 10.1007/s12306-010-0054-y
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical variation of the lateral femoral cutaneous nerve in relation to the anterior superior iliac spine and the iliac crest

Abstract: The location of lateral femoral cutaneous nerve (LFCN) in relation to the anterior superior iliac spine (ASIS) and the iliac crest was investigated in 96 embalmed cadaveric specimens. Fifty-six nerves (58.3%) passed medial to the ASIS. Twenty-two nerves (22.9%) passed at the ASIS. Eighteen nerves (18.8%) passed lateral to the ASIS. The LFCN is usually located at 2.1 +/- 0.8 to 3.9 +/- 1.0 cm below the crest in the range of 2-5 cm lateral to the ASIS, respectively. When the anterior iliac crest bone graft harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 26 publications
5
17
1
1
Order By: Relevance
“…1). These results are consistent with previous observations, wherein a lateral course of the LFCN was found in 4% to 19% of cases 19,20,25,47,48 . In particular, a lateral course of an LFCN branch must be considered in cases when a proximal extension of the anterior approach to the hip joint is needed.…”
Section: Course O F T H E Lat E R a L Femoral Cutaneous N E Rv E W I supporting
confidence: 93%
“…1). These results are consistent with previous observations, wherein a lateral course of the LFCN was found in 4% to 19% of cases 19,20,25,47,48 . In particular, a lateral course of an LFCN branch must be considered in cases when a proximal extension of the anterior approach to the hip joint is needed.…”
Section: Course O F T H E Lat E R a L Femoral Cutaneous N E Rv E W I supporting
confidence: 93%
“…Mischkowski et al (2006) found the nerve superolateral to the ASIS in 2.9% cases, Aszmann et al (1997) andde Ridder et al (1999) in 4% of specimens, and Murata et al (2000) in 13% of cases. Kosiyatrakul et al (2010) reported that 58.3% of the LFCN passed medial to the ASIS, 22.9% passed at the ASIS, and 18.8% passed lateral to it.…”
Section: Discussionmentioning
confidence: 99%
“…The study included the following 12 (a-m) secondary outcomes: (a) distance from the proximal margin of the anesthetized area to the greater trochanter after the LFC nerve block; (b) distance from the proximal margin of the anesthetized area to the greater trochanter after the SI-FIC block; (c) distance from the distal margin of the anesthetized area to the tibiofemoral joint line after the LFC nerve block; (d) distance from the distal margin of the anesthetized area to the tibiofemoral joint line after the SI-FIC block (the distal extent of the SI-FIC block was not measured beyond the tibiofemoral joint line; in case of anesthesia distal to the joint line, the distance was registered as 0 cm); (e) inclusion of each marked surgical incision line in the anesthetized area after the LFC nerve block (total, partial, or absent inclusion); ( f ) success rate of total inclusion of the distal locking incision of the long intramedullary (IM) nail; (g) anteromedial and posterolateral extent of the anesthetized area after the LFC nerve block; (h) frequency of motor block of the femoral nerve after the LFC nerve block (motor block was defined as at least 25% reduction in MVIC compared with baseline measurements); (i) frequency of motor block of the femoral nerve after the SI-FIC block; ( j) duration of anesthesia after the LFC nerve block; (k) quality of ultrasonographic visualization of the LFC nerve inside the FFFT (good, reduced, poor); (l) LFC nerve block performance time; (m) discomfort during LFC nerve block performance (numeric rating scale [NRS] 0-10 from no discomfort [0] to worst imaginable discomfort [10]). …”
Section: Secondary End Pointsmentioning
confidence: 99%